CONVERSATION ANALYSIS OF TURN-TAKING FEATURES IN DRAG RACE PHILIPPINES SEASON 1 UNTUCKED! - Fajardo, Dan Fereth; Oliveros, Nemuel (Journal of English Education and Linguistics, 2026)
The purpose of this study is to determine the turn-taking features utilized in the first season of Drag Race Philippines: Untucked, and their implications in the conversations, through the use of conversation analysis. The researchers employed a qualitative research design to answer the research question; and for the conversations to be transcribed, the researchers applied the Jefferson transcription system to yield the result of the analysis. In conclusion, mention, overlap, interruption, back channel, taking the floor/starting up, yielding the floor, and holding the floor were all observed. The findings also explained several significant factors behind the utilization of the features as well as their specific implications in the course of the conversations.